2009
DOI: 10.1088/0957-4484/20/45/455702
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial nanocables of p-type zinc telluride nanowires sheathed with silicon oxide: synthesis, characterization and properties

Abstract: Coaxial nanocables with a single-crystalline zinc telluride (ZnTe) nanowire core and an amorphous silicon oxide (SiO(x)) shell have been synthesized via a simple one-step chemical vapor deposition (CVD) method on gold-decorated silicon substrates. The single-crystal ZnTe nanowire core is in zinc-blende structure along the [111] direction, while the uniform SiO(x) shell fully covers the core with no observable pin-hole or crack. Formation mechanisms of the ZnTe-SiO(x) nanocables are discussed. The ZnTe nanowire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…The SEM images of the composite samples ( show that the presence of rGO causes efficient charge transfer from the conduction band of ZnSe/ZnTe to rGO sheets which results in quenching of the emission band in the composites. 36 The improved optical absorption and signicant quenching of the emission band of the composites are advantageous for optoelectronic and photonic device applications.…”
Section: Resultsmentioning
confidence: 99%
“…The SEM images of the composite samples ( show that the presence of rGO causes efficient charge transfer from the conduction band of ZnSe/ZnTe to rGO sheets which results in quenching of the emission band in the composites. 36 The improved optical absorption and signicant quenching of the emission band of the composites are advantageous for optoelectronic and photonic device applications.…”
Section: Resultsmentioning
confidence: 99%
“…The p-type characteristic of the unintentionally doped ZnTe NRs (also for ZnTe in other forms) was suggested to originate from the acceptor defects such as Zn vacancies in the materials [122]. Cao et al demonstrated the one-step growth of coaxial p-ZnTe/SiO x nanocables by thermal evaporation [123]. The SiO x shell was insulative and could sever directly as a dielectric layer, facilitating the integration of ZnTe NWs in FETs and chemical and biological sensors.…”
Section: Zntementioning
confidence: 99%
“…p-ZnSe, p-CdTe, p-ZnTe, metals with high work functions, i.e., Au, Pd and Ni have exhibited reliable Ohmic contacts [52,77,[123][124][125].…”
Section: Electrode/semiconductor Contactmentioning
confidence: 99%
“…18,19 Traditional silica coating process is carried out by carbothermal reduction of SiO 2 nanomaterials with active carbon at temperatures higher than 1250 C in owing nitrogen atmosphere. [20][21][22][23][24][25] Afzaal et al provided a route to prepare PbS/ SiO 2 coaxial structure by chemical vapor deposition (CVD) method on silicon substrate at temperature between 650 and 700 C. 26 Zhang et al 27 and Shi et al 28 have employed a laser ablation method to synthesize the coaxial nanostructure containing a silica inter-layer and carbon outer-shell. For fabricating Ge-SiO 2 core-shell nanostructure, Huang et al reported a conventional furnace system to prepare Ge-SiO 2 nanotubes.…”
Section: Introductionmentioning
confidence: 99%